The possibility of using representative actions to pursue claims resulting from the Dieselgate scandal – the future of redress for infringements of collective consumer interests - Urbanek, Anna (Vilnius University Open Series, 2020)
Since the disclosure of unethical and illegal solutions used by Volkswagen A.G. during exhaust emission tests in many countries, proceedings are underway to impose an appropriate penalty on the company and to compensate the victims. On a global scale, the USA, Australia, South Korea and Canada can be mentioned. The European Union is not standing still. Until mid-February 2020, national courts and administrative bodies imposed various types of sanctions in Spain, Germany, Portugal, the Netherlands, Austria and Poland, among others. However, although the Volkswagen case is an infringement of collective consumer interests on a pan-European scale, Member States are resolving the problem through internal proceedings. Does this ensure effective and adequate compensation of affected consumers? The increase in protection would ensure, among other things, that there is a valid injunction for adequate compensation and that the proceedings are international in nature. The paper aims to show how the representative actions mechanism proposed in the “New Deal for Consumers” package could affect the effectiveness of decisions taken in the Volkswagen case by Member States’ competent authorities.
Keywords: consumer protection; New Deal; representative actions